Stressing out-carp edema virus induces stress and modulates immune response in common carp - Zawisza, Maria; Rebl, Alexander; Teitge, Felix; Krzystyniak, Barbara; Piackova, Veronika; Gela, David; Kocour, Martin; Chadzinska, Magdalena; Adamek, Mikolaj; Rakus, Krzysztof (Frontiers in immunology, 2024)
INTRODUCTION: Carp edema virus (CEV) is a fish poxvirus that primarily infects the gills of common carp. CEV causes koi sleepy disease (KSD), which is highly contagious and can result in mortality of up to 100%. METHODS: In the present study, we analyzed the stress and immune responses during KSD in two strains of common carp with different resistance to CEV: susceptible koi and resistant Amur sazan. Experiments were performed at two temperatures: 12°C and 18°C. In the case of koi carp, we also analyzed the effect of supplementation of 0.6% NaCl into tank water, which prevents mortality of the CEV-infected fish (salt rescue model). RESULTS: We found that CEV-infected koi kept at 18°C had the highest viral load, which correlated with the most severe histopathological changes in the gills. CEV infection resulted in the activation of stress response reflected by the upregulated expression of genes involved in stress response in the stress axis organs and increased levels of cortisol and glucose in the blood plasma. These changes were the most pronounced in CEV-infected koi kept at 18°C. At both temperatures, the activation of antiviral immune response was observed in koi kept under freshwater and NaCl conditions upon CEV infection. Interestingly, a clear downregulation of the expression of adaptive immune genes was observed in CEV-infected koi kept under freshwater at 18°C. CONCLUSION: CEV induces a stress response and modulates adaptive immune response in koi, and this is correlated with the level of viral load and disease development.
Keywords: koi sleepy disease; imunita; Poxviridae Infections; zvířata; Immunity; Sodium Chloride; infekce vyvolané poxviry; common carp; Animals; chlorid sodný; immunomodulation; fish poxviruses; stress; nemoci ryb; Edema; kapři; carp edema virus; Carps; edém; CEV; Fish Diseases